Methodologies development and analysis for obtaining boundary conditions of heat transfer in a linear motor driven stage - Chow, Kelvin Joon Ho (2013)
Permanent magnet linear motors have been increasingly used in many machine applications that need precise and high speed motions since the last decade. A major drawback which is the heat trap in the coil cannot be dissipated to the environment fast enough, and much of the heat is transferred to the carriage The thermally induced deformations and stresses of the carriage, due to high heat influx from the coil, will distort the carriage and any specimens fix on the carriage top. The resulting distortion will produce a positioning error. The lumped-parameter method is adopted here to model the temperature and heat flux from the joining top of the coil to the carriage. The model has several essential elements such as a heat source sub-model, heat loss convective coefficients for complex geometry, and contact conductance values between structure parts. The developed method for predicting the positioning error is real-timed and flexible to any process of a specific precision machine structure.